Imunoexpressão do c-kit em Osteossarcomas Humanos: Correlação com parâmetros anátomo-patológicos, clínicos e testes in vitro - Miiji, Luciana Nakao Odashiro [UNIFESP] (2009)
Purpose: To investigate the immunoexpression and its prognostic relevance of KIT in patients with osteosarcomas and the effect of Imatinib mesylate (STI571) on proliferation and invasion of human cell osteosarcoma line. Material and Methods: A retrospective immunohistochemical study was performed on archival formalin fixed paraffin-embedded tissue obtained from Department of Pathology of Federal University of São Paulo of 52 high-grade patients with primary osteosarcomas of extremities treated at the Instituto de Oncologia Pediátrica. Only pre-chemotherapy specimens were analysed. Strong cytoplasmic and membranous staining cases were taken as positive. The human cell line MG 63 was incubated and inhibitory effect of STI571 on cell proliferation and invasion was studied. Results: Twenty four cases (46,15%) expressed c-kit and tumours ckit positive had lower necrosis pos chemotherapy. No correlation was found between ckit expression and overall and disease free survival. STI571 inhibited the rates of cell growth of osteosaroma cells in low doses and invasion in high doses Conclusions: Tumours c-kit positives had worse response to chemotherapy and STI571 plays a role in blocking or slowing the rate of growth of osteosarcoma cells expressing ckit, but not the invasive capacity of these neoplastic cells. These data suggested that Imatinib Mesylate could be a therapeutic target of strategies against Osteosarcoma that express c-kit.